Impact of anesthesia type on postoperative pain and outcomes in primary hip and knee arthroplasty: a retrospective register analysis - Sponheuer, Keno; Becker-Rux, Diana; Scheike, Stephan; Barsch, Lukas; Pempe, Christina; Pfrepper, Christian; Roth, Andreas; Werdehausen, Robert (BMC anesthesiology, 2025)
Background This study explores the effects of single-sided spinal versus general anesthesia on patients undergoing hip and knee arthroplasty within a fast-track surgery environment. Although many studies suggest better outcomes with neuraxial anesthesia in lower extremity joint replacement, its benefits in fast-track surgery remain unclear. Methods A retrospective analysis was performed on data derived from 283 patients. We focused on patients who had undergone primary, elective, and unilateral endoprosthetic fast-track hip or knee joint replacement surgeries between May 15, 2019, and November 30, 2020. The primary objective was to ascertain the correlation between the type of anesthesia and several postoperative parameters, including pain intensity, analgesia requirements, incidence of postoperative nausea and vomiting, perioperative process times, and hospital length of stay, based on the collected data. Results Our findings indicated no difference in pain intensity and patient satisfaction between the general (n = 195) and single-sided spinal anesthesia (n = 61) groups at the first postoperative day. However, a notable difference was observed in the recovery room, with patients under spinal anesthesia requiring significantly less piritramide than those after general anesthesia. Both groups had a similar incidence of postoperative nausea and length of hospital stay. Conclusions When analyzed retrospectively, the type of anesthesia applied is not associated with an increased risk of postoperative pain, postoperative nausea and vomiting, or prolonged hospital stay. Overall, neither anesthesia method outperforms the other concerning patient satisfaction, emphasizing the importance of patient preference and individual risk factors in the decision-making process.